Electrical Properties of Zn-Phthalocyanine and Poly (3-hexylthiophene) Doped Nematic Liquid Crystal - Karakus, Y.; Okutan, M.; Kosemen, A.; San, S. E.; Alpaslan, Z.; Demir, A. (HINDAWI LTD, 2011)
An E7 coded nematic liquid crystal was doped with zinc phthalocyanine and poly (3-hexylthiophene). A variety of properties including relaxation time, absorption coefficient, and critical frequency of this doped system were investigated using impedance spectroscopy. The doped systems displayed increased absorption coefficients in the range 0.22-0.55 and relaxation times from 5.05 x 10(-7) s to 3.59 x 10(-6) s with a decrease in the critical frequency from 3.54 MHz to 2.048 MHz.
Keywords: DIELECTRIC-RELAXATION; POLYTHIOPHENE; EFFICIENCY; IMPEDANCE; Science & Technology - Other Topics; Materials Science